2014
DOI: 10.1037/a0034734
|View full text |Cite
|
Sign up to set email alerts
|

The flexible focus: Whether spatial attention is unitary or divided depends on observer goals.

Abstract: The distribution of visual attention has been the topic of much investigation, and various theories have posited that attention is allocated either as a single unitary focus or as multiple independent foci. In the present experiment, we demonstrate that attention can be flexibly deployed as either a unitary or a divided focus in the same experimental task, depending on the observer's goals. To assess the distribution of attention, we employed a dual-stream Attentional Blink (AB) paradigm and two target pairs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 42 publications
(63 reference statements)
2
49
0
2
Order By: Relevance
“…More specifically, they extend this literature by demonstrating that when a given situation would benefit from object-based visual attention, only those with the available cognitive resources-such as WMC-will use object-based attention. Moreover, recent research has suggested that people can also attend multiple independent locations at a time (Jefferies et al, 2014). These findings suggest that high-and low-spans should differ in this ability, as well.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…More specifically, they extend this literature by demonstrating that when a given situation would benefit from object-based visual attention, only those with the available cognitive resources-such as WMC-will use object-based attention. Moreover, recent research has suggested that people can also attend multiple independent locations at a time (Jefferies et al, 2014). These findings suggest that high-and low-spans should differ in this ability, as well.…”
Section: Discussionmentioning
confidence: 87%
“…The highest resolution of attention then comes from information closest to the center of the spotlight of attention, with lower resolution of attention farther from the center (Arrington, Carr, Mayer, & Rao, 2000;LaBerge, 1983;LaBerge & Brown, 1989;Posner, Snyder, & Davidson, 1980). However, others argue that cued visual attention does not work as a spotlight, and is instead based on expectations of the appearance within a shape or object-such as a square or a ring (Bleckley et al, 2003;Egly & Homa, 1984;Jefferies, Enns, & Di Lollo, 2014;Neisser & Becklen, 1975).…”
mentioning
confidence: 99%
“…The experiment was 1 Several recent studies did demonstrate Lag-1 sparing when T1 and T2 were presented in two different RSVP streams (Jefferies & Di Lollo, 2009;Jefferies, Enns, & Di Lollo, 2014;Jefferies, Ghorashi, Kawahara, & Di Lollo, 2007;Potter, Staub, & O'Connor, 2002;Shih, 2000). However, Jefferies and colleagues suggested that participants' attention was spread across the two streams, leading the two streams to be processed as one location.…”
Section: Apparatusmentioning
confidence: 99%
“…Duncan et al (1994) presented two masked targets at different spatiotemporal offsets and observed what they termed an attentional dwell time, which resembles in many ways an attentional blink, except that the targets were presented approximately 2-4 degrees apart and without RSVP. Many other experiments have demonstrated variations of the attentional blink across different locations for targets presented either in isolation, or in ongoing RSVP streams with spatial separations ranging from .5 to 9 degrees of visual angle (Bay & Wyble, 2014;Du, Abrams, & Zhang, 2011;Jefferies & Di Lollo, 2009;Jefferies, Enns, & Di Lollo, 2014;Kawahara & Yamada, 2006;Jefferies, Ghorashi, Kawahara, & Di Lollo, 2007;Kristjánsson & Nakayama, 2002;Shih, 2000;Visser, Bischof, & Di Lollo, 1999).…”
Section: The Attentional Blink and The Attentional Dwell Timementioning
confidence: 99%